Structure Elucidation of Two Unknown Oxydic Degradation Impurities of Rifaximin - Liu, Chao; Hu, Chang-Qin; Jin, Shao-Hong (Asian Journal of Chemistry, 2011)
Rifaximin is a semi-synthetic rifamycin derivate. Two unknown oxydic degradation impurities (impurity 1 and impurity 2) were prepared from rifaximin based on the degradation mechanism by using manganese dioxide as the oxidant. The structure of the impurities was elucidated by using MS and other modern spectroscopic (NMR and FTIR) techniques and as (2S,20S,21S,22R,23R,24R,25S,26R,27S)-6,21,23-trihydroxy-27-methoxy-2,4,16,20,22,24,26- h e p t a m e t h y l - 1 1 - m e t h y l e n e - 1 , 5 , 1 5 - t r i o x o - 1 , 2 , 5 , 1 1 - t e t r a h y d r o - 2 , 7 - (epoxypentadeca[1,11,13]trienoimino)furo[2'',3'':7',8']naphtho[1',2':4,5]imidazo[1,2-a]pyridin- 25-yl-acetate and (2S,20S,21S, 22R,23R,24R,25S,26R,27S)-5,21,23-trihydroxy-27-methoxy- 2,4,16,20,22,24,26-heptamethyl-11-methylene-1,6,15-trioxo-1,2,6,11-tetrahydro-2,7- (epoxypentadeca[1,11,13]trienoimino)furo[2'',3'':7',8']naphtho[1',2':4,5]imidazo[1,2-a]pyridin- 25-yl-acetate by IUPAC.